Structural characterization of gephyrin by AFM and SAXS reveals a mixture of compact and extended states. (8th October 2013) - Sander, Bodo; Tria, Giancarlo; Shkumatov, Alexander V.; Kim, Eun‐Young; Grossmann, J. Günter; Tessmer, Ingrid; Svergun, Dmitri I.; Schindelin, Hermann
<x xml:space="preserve">Abstract</x> Gephyrin is a trimeric protein involved in the final steps of molybdenum‐cofactor (Moco) biosynthesis and in the clustering of inhibitory glycine and GABAA receptors at postsynaptic specializations. Each protomer consists of stably folded domains (referred to as the G and E domains) located at either terminus and connected by a proteolytically sensitive linker of ∼150 residues. Both terminal domains can oligomerize in their isolated forms; however, in the context of the full‐length protein only the G‐domain trimer is permanently present, whereas E‐domain dimerization is prevented. Atomic force microscopy (AFM) and small‐angle X‐ray scattering (SAXS) reveal a high degree of flexibility in the structure of gephyrin. The results imply an equilibrium between compact and extended conformational states in solution, with a preference for compact states. CD spectroscopy suggests that a partial compaction is achieved by interactions of the linker with the G and E domains. Taken together, the data provide a rationale for the role of the linker in the overall structure and the conformational dynamics of gephyrin.